Social prescribing programs involving unpaid caregivers: A scoping review - Zeest Kadri; Amal Khan; Maheen Raja; Jenna Smith-Turchyn; Jennifer Watt; Allison Williams (PLoS ONE, 2026)
Unpaid caregivers face significant health challenges due to the sustained demands of their roles. Social prescribing is a model of care that may help unpaid caregivers connect with non-medical community-based support systems to improve their health and well-being. Given the growing interest in social prescribing, there is a need to map out existing literature to understand its potential to support caregiver health. This scoping review describes the current landscape of social prescribing programs for unpaid caregivers. A protocol was previously published on Open Science Framework. We searched academic and grey literature from January 2000 to March 2025, following Arksey and O’Malley’s framework and JBI recommendations for scoping reviews. An inductive approach was used to analyse data in order to generate descriptive summaries and themes of program and outcome characteristics. We identified 17 studies for inclusion from 4376 titles and abstracts. Most programs were designed for both caregivers and care recipients to participate in together and involved a variety of self, provider and community-based referral pathways. Programs included nature, art, museum and physical activity-based experiences, and most were facilitated by a supervisor or coach. Program features varied, offering caregivers spaces to connect and socialize, strengthen their relationship with the care recipient, or express themselves creatively. Studies reported positive impacts on caregiver stress, the caregiver-care recipient relationship, and social connection. Logistical benefits such as low cost and accessibility, as well as challenges like transportation and scheduling were reported to influence program attendance and retention. While this review highlights the potential of social prescribing to support caregiver health, future research should explore opportunities to integrate programs within respite care, develop more structured referral pathways and evaluate the full social prescribing pathway in addition to virtual programming options to ensure effective implementation within broader health and social care systems.